Effect of postoperative cognitive dysfunction on rehabilitation of patients after cardiac valve replacement surgery - DUAN Zhenxin (Di-san junyi daxue xuebao, 2019)
Objective To determine the effect of postoperative cognitive dysfunction (POCD) on postoperative rehabilitation of the patients undergoing heart valve replacement. Methods A total of 252 patients (104 males and 148 females, at an age of 47.1±8.8) who were prospectively scheduled for cardiac valve replacement surgery in our hospital from October 2016 to June 2018 were enrolled, and their clinical data were collected and retrospectively analyzed. The cognitive function of the patients was assessed by neuropsychological tests at 1 d before and 7 d after operation. Cognitive function assessment was carried out in 1 d before and in 7 d after surgery. According to the results, the patients were divided into POCD group (group P) and non-POCD group (group N). Unconditional logistic regression analysis was performed to screen the risk factors for POCD. With age and anesthesia as covariates, the 252 patients were played to 1 :1 propensity score matching to obtain 100 patients (39 male and 61 female patients, 48.5±9.6 years old), and the postoperative hospital stay, postoperative complications, activity conditions, and cardiac function were analyzed between the 2 groups (n=50). Results ① The patients of groupPhad significantly longer lengths of ICU stay (3.9±1.6 vs 3.3±0.7 d, P=0.012) and of hospital stay (23.1±7.3 vs 19.5±4.1 d, P=0.003) than those of the group N. ② The Katz Index activity score on the 7th day after surgery was obviously lower in the groupPthan the groupN(2.9±1.1 vs 3.4±0.8, P=0.025). ③ There was no significant difference in cardiac function between the 2 groups after operation. Conclusion POCD significantly delays postoperative rehabilitation time and reduces postoperative activity in the patients undergoing heart valve replacement surgery, but it has no effect on postoperative cardiac function.